Allevare uomini. Sulla “seconda natura” in Kant - Russo, Marco (Mechane, 2025)
The “second nature” formula indicates the distancing from nature through culture, which “raises men” by means of artifices. We compare Sloterdijk’s thesis, according to which culture is exclusively anthropotechnics, with the humanistic thesis, according to which education should use technique also for non-technical purposes. An influential modern humanistic model can be found in the training of the Renaissance courtier outlined by Castiglione. Through various steps, the model flows into the process of civilization that for Kant leads to second nature. The article discusses how this completely artificial second nature is to be interpreted and shows that its Endzweck (final end) is moral life, which is irreducible to the technical-practical reason acting in civil society and in the epistemic rationalization of nature.